Biến tính ghép axit acrylic lên chitin bằng phương pháp chiếu xạ để hấp phụ ion Zn2+ và Cu2+ - Hạnh, Trương Thị; Hiến, Nguyễn Quốc; Huy, Hà Thúc (Vietnam Journal of Chemistry, 2014)
Partially deacetylated chitin (PD/chitin) was modified by irradiation grafting with acrylic acid (AAc) for various concentrations of 5, 10, 15, 20% at dose up to16 kGy and dose rate of 1.6 kGy/h. The dependence of the grafting rate (Vg) onto monomer concentration (M) was determined to be Vg = k[M]1.09. Equilibrium isotherms for the adsorption of heavy metal ions (Zn2+, Cu2+) onto grafted PD/chitin have been also investigated.